2020
DOI: 10.1111/tpj.14653
|View full text |Cite
|
Sign up to set email alerts
|

Two combinatorial patterns of telomere histone marks in plants with canonical and non‐canonical telomere repeats

Abstract: Telomeres, nucleoprotein structures at the ends of linear eukaryotic chromosomes, are crucial for the maintenance of genome integrity. In most plants, telomeres consist of conserved tandem repeat units comprising the TTTAGGG motif. Recently, non-canonical telomeres were described in several plants and plant taxons, including the carnivorous plant Genlisea hispidula (TTCAGG/TTTCAGG), the genus Cestrum (Solanaceae; TTTTTTAGGG), and plants from the Asparagales order with either a vertebrate-type telomere repeat T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 49 publications
(59 reference statements)
0
20
0
Order By: Relevance
“…Owing to their repetitive nature (Fojtová and Fajkus, 2014; Majerová et al, 2014; Vaquero-Sedas et al, 2011, 2012; Vega-Vaquero et al, 2016), the chromatin composition and organization of plant telomeres has long remained enigmatic (Achrem et al, 2020; Dvořáčková et al, 2015). ChIP dot-blot analyses indicated a dominance of H3K9me2 over H3K27me3 histone marks but some of the Arabidopsis telomere regions also display euchromatic H3K4me2/3 marks (Adamusová et al, 2020; Grafi et al, 2007; Vaquero-Sedas et al, 2011). Here, combining ChIP-seq, ChIP dot-blot with telomeric probes and in situ immunolocalization showed that H1 moderates by 2-to-4 fold the accumulation of this mark on telomeres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to their repetitive nature (Fojtová and Fajkus, 2014; Majerová et al, 2014; Vaquero-Sedas et al, 2011, 2012; Vega-Vaquero et al, 2016), the chromatin composition and organization of plant telomeres has long remained enigmatic (Achrem et al, 2020; Dvořáčková et al, 2015). ChIP dot-blot analyses indicated a dominance of H3K9me2 over H3K27me3 histone marks but some of the Arabidopsis telomere regions also display euchromatic H3K4me2/3 marks (Adamusová et al, 2020; Grafi et al, 2007; Vaquero-Sedas et al, 2011). Here, combining ChIP-seq, ChIP dot-blot with telomeric probes and in situ immunolocalization showed that H1 moderates by 2-to-4 fold the accumulation of this mark on telomeres.…”
Section: Discussionmentioning
confidence: 99%
“…A role for H1 in telomere chromatin composition and sub-nuclear positioning Considering that telomeres display a continuum of perfect telobox motifs and a propensity to attract TRB proteins (Schrumpfová et al, 2014), we assessed whether these chromosome domains were, similar to ITRs, subject to H3K27me3 enrichment in 2h1 plants. Because the perfect continuum of terminal telomeric motifs is not suited for quantitative NGS analyses, we examined telomeric H3K27me3 using dot-blot hybridization of anti-H3K27me3 and anti-H3 ChIP DNA to radioactively labeled concatenated telomeric probes (Adamusová et al, 2020). This led to the estimation that telomeres display an average ~4-fold H3K27me3 enrichment in 2h1 as compared to WT plants, independent of any detectable change in nucleosome occupancy ( Figure 6A and S14).…”
Section: H1 Excludes the Gh1-containing Telomere Repeat Binding 1 Promentioning
confidence: 99%
“…The epigenetic nature of telomeres and subtelomeres remains controversial ( Vaquero-Sedas and Vega-Palas 2011 , Galati et al 2013 , Ichikawa et al 2015 , Adamusová et al 2019 ). In the classic model, animal and plant telomeres were interpreted as heterochromatic structures ( Kavi et al 2005 , Postepska-Igielska et al 2013 ).…”
Section: Epigenetic Regulation Of Telomere and Subtelomere Regionsmentioning
confidence: 99%
“…Similar results were obtained in studies on plant telomeres. In Arabidopsis , heterochromatin modifications, such as H3K9me2 and H3K27me3, as well as euchromatin H3K4me3 modification have been reported ( Vrbsky et al 2010 , Majerová et al 2014 , Adamusová et al 2019 ). This occurrence of both heterochromatin and euchromatin modifications in the Arabidopsis telomere region was defined as the presence of an “intermediate” heterochromatin ( Vrbsky et al 2010 , Majerová et al 2014 ).…”
Section: Epigenetic Regulation Of Telomere and Subtelomere Regionsmentioning
confidence: 99%
“…One of them corresponds to the Arabidopsis-like pattern, where telomere histones are marked predominantly with H3K9me2. The other one is the tobacco-like pattern marked predominantly with H3K27me3 (Adamusová et al, 2019).…”
Section: Session 1: a View On Chromatin Techniques And Nuclear Strumentioning
confidence: 99%